Effectiveness of Gong’s Mobilization Over Myofascial Release Technique in Patients with Adhesive Capsulitis.: Life Sciences-Physiotherapy - Challey, Tilling; Dutta2, Abhijit; Kalita, Abhijit; Pyngrope4, Hormot Ryniaw (International Journal of Life Science and Pharma Research, 2023)
Adhesive Capsulitis, also known as frozen shoulder, is a severe condition of the shoulder characterized by pain, severe stiffness and restriction of movements in the shoulder joint. We aim to evaluate the effect of Gong's Mobilization with conventional therapy versus the Myofascial release technique with conventional treatment in subjects with Adhesive capsulitis; Objectives that were assessed are Shoulder pain, disability and range of motion. Thirty subjects completed the study. The subjects were randomly assigned into two groups. Group A Received Gong's Mobilization with conventional therapy, and Group B received Myofascial Release technique with traditional treatment. Both groups received ten intervention sessions (5 sessions/week) in 2 weeks. Outcome Parameters: Pain intensity was measured by Visual Analogue Scale (VAS), ROM of the shoulder by universal goniometer & functional disability by shoulder pain and disability index (SPADI). These parameters were measured pre-intervention and after ten sessions of intervention. Analysis using paired t-test and independent-test found no statistically significant difference (p<0.05) between Gong's mobilization with the conventional therapy group and Myofascial release technique with the traditional group of therapy on improving pain, ROM and decreasing the functional deficit. Gong's mobilization with conventional therapy and Myofascial release with the standard treatment technique with conventional therapy is equally effective in improving pain and ROM and decreasing the functional deficit.